An Electrochemical Acetylcholinesterase Biosensor Based on Fluorene(bisthiophene) Comprising Polymer for Paraoxon Detection. Issue 3 (5th September 2022) - Celik, Huzeyfe; Soylemez, Saniye
Abstract: In this study, a novel conductive polymer comprising biosensor based on poly‐2, 2′‐(9, 9‐dioctyl‐9 h‐fluorene‐2, 7‐diyl)bistiophene (Poly(BT)) and acetylcholinesterase (AChE) was reported for the determination of paraoxon. This practical biosensor allowed to catalyze electrochemical oxidation of acetylthiocholine (+0.6 V vs. Ag reference). The detection range for acetylcholine chloride (AThCl) with Poly(BT)/AChE was found to be 0.025–4 mM. In pesticide analysis, wide linear ranges from 0.5 to 1 μg/L and 1 to 14 μg/L, and a low detection limit of 0.033 μg/L were estimated. Under optimum operating conditions, the developed biosensor was used for pesticide detection in milk and tap water samples, effectively. Abstract :